IDENTITAS LOKAL SIDOARJO DALAM KOREOGRAFI BANJAR KEMUNING KARYA AGUSTINUS HERI SUGIANTO - Arum Trianingsih Hermawan; Pramutomo Pramutomo (Greget, 2021)
Sidoarjo is known to have the city icon “Shrimp and Milkfish” because it has an area located on the coast and part of the livelihood of the community is fishermen. Coastal communities have distinctive cultural traits and characteristics with the habit of processing marine products. Sedekah Laut or Petik Laut is one of the cultures owned by the coastal community of Sidoarjo which is manifested in the form of the Banjar Kemuning dance. This study seeks to uncover problems related to local identity expressed in the choreography of the Banjar Kemuning dance.  The research problems were analyzed based on the theory of culture and identity, the theory of choreographic concept analysis, the theory of art and identity and the theory of expression. This research is qualitative with data collected through literature study, interviews, and observations of Banjar Kemuning Dance. The results showed that the components of the Banjar Kemuning dance include: (1). Choreography, (2). Accompaniment music; poetry and narration, and (3). Clothing, (4).Properties that as a whole reflect the lives of coastal communities who are active, dynamic and do not forget to be grateful for the marine products they get from God Almighty in the form of a complete unity of the Banjar Kemuning dance.